(untitled) (Mustansiria Dental Journal, 2025)
Aims: The purpose of this research was to evaluate the knowledge and awareness of undergraduate medical and dental students from various Iraqi universities regarding oral cancer. Methods: A cross-sectional survey was conducted, and questionnaires were distributed to 378 students. Awareness and knowledge of oral cancer were assessed through questions related to examinations, patient history, risk factors for oral cancer, and the clinical appearance of oral cancer.Results: Dental participants reported significantly higher percentages (84.8%) for routine oral examinations compared to medical students (50.4%). Smoking was identified as a risk factor by 90.8% of medical students and 77.0% of dental students. A very small percentage of both dental (9.7%) and medical (5.0%) students felt they were very well informed about the clinical appearance of oral cancer. Regarding oral changes associated with oral cancer, 70.6% of medical students and 56.8% of dental students recognized leukoplakia. The majority of medical (91.6%) and dental (94.9%) students indicated that they needed more information about oral cancer. Conclusions This study identified both strengths and weaknesses in oral cancer knowledge among dental and medical students. While dental students displayed greater awareness in certain areas, the overall findings emphasize the need for ongoing education and training.